Treatment options for leishmaniasis. (20th October 2021) - Pradhan, S.; Schwartz, R.A.; Patil, A.; Grabbe, S.; Goldust, M.
Summary: Leishmaniasis is broadly classified into three types: cutaneous, mucocutaneous and visceral. The visceral form is most dangerous and can result in death. Although leishmaniasis is an ancient disease, its treatment is still challenging. Several drugs, differing in their cost, toxicity, treatment duration and emergence of drug resistance, are used for different types of leishmaniasis. To overcome these limitations, the search for newer drugs and other treatments continues. In this article, we discuss conventional drugs, other treatments, including newer options such as immunotherapy and immunochemotherapy, and future prospects for leishmaniasis treatment.